Outdoor Tourist Destination: Sumur Batu Art Sacred Space - L. Edhi Prasetya; Yuke Ardhiati; M. Wira Abi; Chandra Arfiansyah; M. Rifqie Izzulhaq; Raditya Raka Putra (Catuspata Press, 2021)
Purpose: This study aims to find how a sacred space be a part of outdoor tourist destination consisting of heritage building law and rules to respect the sacred space. Research methods: The study is based on a qualitative research by accommodating criterias of heritage building rules and considering the local architecture as base design. Findings: Sumur Batu is a heritage-listed object in Bekasi. It is a water well that believed by local peoples to be an ancestral heritage and is named Tirta Karuhun. The site is one of the Satellites of The National Gallery of Indonesia (GNI) that plays a role as an art gallery that shows artworks. Implication: The site enriches the contemporary art displays in a sacred area. The sacred place has opportunity to be a venue for art activities. It can be an outdoor tourist destination.